Caracterização genética populacional do dourado, Salminus brasiliensis (Pisces, Characidae, Salmininae) na Bacia do alto e médio rio Uruguai - Ribolli, Josiane (Universidade Federal de São Carlos, 2014)
brasiliensis (CUVIER, 1816) is distributed in several basins of South America. Commonly known by dourado, is a large fish and economical and social importance for artisanal and sport fishing. Due to the necessity of conservation and the absence of knowledge about the genetic structure of Neotropical migratory fish, the present study aimed to infer about the mating system and population genetic parameters of S. brasiliensis from the upper and middle Uruguay River basin. Populations of adult individuals were sampled during two years in the reproductive and non-reproductive periods in the upper and middle river Uruguay. The larvae of this species were obtained from natural spawning in the upper Uruguay River basin. Genetic analyses were performed using microsatellite markers to infer parameters of genetic diversity, population structure and estimation of kinship. All populations evaluated in this study showed high levels of genetic diversity. For the first reproductive period four genetically distinct populations were identified, one corresponding to the beginning of breeding season, two to the intermediate period and one to the end of the spawning season. The populations analyzed during the non-reproductive period were genetically different between the two years of study. Both populations of reproductive and nonreproductive period did not reveal any isolation by distance in the downstream of HPP Itá area. No bottleneck effect was observed in the populations sampled in the region fragmented by hydroelectric dams; however, the populations under the influence of the dams presented small effective population sizes. The results revealed no genetic structure among populations situated upstream and downstream of the Hydroelectric Power Plant (HPP) Machadinho and a particular differentiation between populations sampled upstream and downstream the HPP Itá, due, probably, of the barrier resulting from the preexisting of geographical barrier in the Uruguay River, Augusto César Gorge. The analyses of kinship indicated that multiple males and females participated effectively during reproduction and spawning of S. brasiliensis evaluated in the environment. The findings of this study provide new insights into the mating system and mode of organization during the reproductive and non-reproductive period of S. brasiliensis. This information must be taken into account in decisions about fisheries management programs and in broodstock samplings and for restocking programs.
Keywords: Genética de populações; Peixe migrador; Sistema de acasalamento; Manejo pesqueiro; Estrutura genética; CIENCIAS BIOLOGICAS::ECOLOGIA